Retention of health workers in Malawi: perspectives of health workers and district management. - NORMAND, CHARLES; MCAULIFFE, EILISH; MAC LACHLAN, MALCOLM; UDUMA, OGENNA (My University, 2009)
Background Shortage of human resources is a major problem facing Malawi, where more than 50% of the population lives in rural areas. Most of the district health services are provided by clinical health officers specially trained to provide services that would normally be provided by fully qualified doctors or specialists. As this cadre and the cadre of enrolled nurses are the mainstay of the Malawian health service at the district level, it is important that they are supported and motivated to deliver a good standard of service to the population. This study explores how these cadres are managed and motivated and the impact this has on their performance. Methods A quantitative survey measured health workers' job satisfaction, perceptions of the work environment and sense of justice in the workplace, and was reported elsewhere. It emerged that health workers were particularly dissatisfied with what they perceived as unfair access to continuous education and career advancement opportunities, as well as inadequate supervision. These issues and their contribution to demotivation, from the perspective of both management and health workers, were further explored by means of qualitative techniques. Focus group discussions were held with health workers, and key-informant interviews were conducted with members of district health management teams and human resource officers in the Ministry of Health. The focus groups used convenience sampling that included all the different cadres of health workers available and willing to participate on the day the research team visited the health facility. The interviews targeted district health management teams in three districts and the human resources personnel in the Ministry of Health, also sampling those who were available and agreed to participate. Results The results showed that health workers consider continuous education and career progression strategies to be inadequate. Standard human resource management practices such as performance appraisal and the provision of job descriptions were not present in many cases. Health workers felt that they were inadequately supervised, with no feedback on performance. In contrast to health workers, managers did not perceive these human resources management deficiencies in the system as having an impact on motivation. Conclusion A strong human resource management function operating at the district level is likely to improve worker motivation and performance.
PUBLISHED
Keywords: Public Health & Primary Care